The Relationship Between Septic Tank Distance And The Biological Quality Of Dug Well Water In Rensing Bat Village, West Sakra District - Iwan Desimal; Dahlia Rosma Indah; M. Hario Tangkas Abqory (Hydrogen: Jurnal Kependidikan Kimia, 2025)
Based on data from the results of the Household Drinking Water Quality Surveillance of the Rensing Health Center in Rensing Bat Village in 2024, which was carried out from 15 wells, there were 13 wells that contained Eschericia colli bacteria  and 2 wells that did not contain Eschericia colli bacteria. This study aims to determine the relationship between the distance of the septic tank and the biological quality of dug well water in Rensing Village, West Sakra District in 2025. This type of research is an analytical survey with a cross sectional approach. This research was conducted in Rensing Bat Village, West Sakra District. The population in this study is 124 houses that have dug wells and septic tanks with a sample of 55 houses taken using systematic random sampling techniques. Data analysis used univariate and bivariate tests. The results of the statistical test  of the septic tank distance variable  showed a value (p value = 0.027<0.05) with the biological quality of the dug well water. Conclusion: there is a relationship between the distance of the septic tank and the biological quality of dug well water in Rensing Bat Village, West Sakra District in 2025. It is recommended to the head of the Rensing Health Center to assign environmental health workers to intensify counseling activities on the safe distance  of septic tanks to dug wells with a distance of ≥ 10 m and cook water before consumption in order to break the chain of water-transmitted diseases. Proper management of the septic tank distance is essential to prevent negative impacts on water quality and to protect public health and the environment.